BRAND EQUITY AND STRATEGIES TO WIN BUSINESS COMPETITION - Iqbal Ramadhani; Marya Mujayana (Journal of Applied Management and Business, 2022)
Business competition has become normal in the business world. Some business people try hard to win the competition. One of his efforts is to build brand strength. Brand strength in business is very important, because it can increase customer loyalty. Brand strength is also able to encourage customer confidence in the products produced. This can not be separated from the customer's perception of the brand reputation. Brands that have a good reputation will provide more revenue than ordinary brands. This study will describe the strength of the brand in winning the business competition. There are seven indicators used in establishing brand strength. The results of the study indicate the fact that building brand equity or strength can encourage customer loyalty and ultimately win the business competition.